Development of Natural Tourism Potential and Digitalization of Nateh Village Hulu Sungai Tengah Through Smart Tourism - Suriansyah, Ahmad; Sari, Raihanah; Agusta, Akhmad Riandy; Pratiwi, Diani Ayu; Noorhapizah; Jannah, Fathul (Research and Social Study Institute, 2022)
The tourist village is one of the natural resources that have the potential to be developed, given the increasing needs of the community, and one of them is a vacation. To form a tourism village, a set of components is needed which consists of management and participation of the community, education about tourists, and good relations with work partners in order to increase people's income. Nateh Village is one of the tourist destinations that promises a lot of natural scenery such as rivers, mountains, and beautiful caves. However, there are still many tourists who are not familiar with this village because the introduction to this village is still lacking. For this reason, the South Kalimantan community sevice team carried out community service in Nateh Village in the form of training on the potential of tourism villages through smart tourism and market digitization. The introduction of tourist villages can be done by using smart tourism as branding for a tourist destination and processed products through digital-based offers and marketing that we often hear with the term tourism digitization. Through this community sevice activity, marketing about the potential of the Nateh tourist village becomes more and more easily found on various social media such as Instagram, Facebook, and websites that directly managed to introduce Nateh village.